FROM WORK PRESSURE TO ENTREPRENEURSHIP: GENERATION Z CONFLICT, INSECURITY, AND STRESS (International Journal of Global Accounting, Management, Education, and Entrepreneurship, 2026)
This study examines the role of work-related stress as a catalyst for Generation Z’s career transition towards entrepreneurship. Amidst the dominance of the informal sector and rising underemployment, poor job quality has led to workplace conflicts, job insecurity and work-related stress becoming increasingly common experiences among young workers. Unlike previous studies that emphasised the negative impacts of work-related stress, this research explores its transformational dimensions in driving alternative career choices. Using a qualitative approach with a phenomenological design, this study delves into the subjective experiences of Generation Z through in-depth interviews analysed thematically. The findings indicate that work pressure develops in stages, progressing from workplace conflict and job insecurity to cumulative work-related stress. These conditions trigger career reflection as a turning point that drives individuals out of formal employment. Key findings suggest that entrepreneurship is not solely driven by opportunities (pull factors), but also by work-related stress as a powerful push factor. Thus, work-related stress is not merely destructive but functions as a catalyst for career transformation. This study offers a novel contribution through an integrative model linking work-related stress and entrepreneurship, whilst affirming the role of work-related stress in the emergence of new entrepreneurs among Generation Z